Functional roles of evolutionary conserved motifs and residues in vertebrate chemokine receptors. Issue 1 (21st November 2014) - Nomiyama, Hisayuki; Yoshie, Osamu
Abstract : Review of structural and signaling roles of evolutionary conserved motifs and residues in vertebrate chemokine receptors. Abstract: Chemokine receptors regulate cell migration and homing. They belong to the rhodopsin-like family of GPCRs. Their ancestor genes emerged in the early stages of vertebrate evolution. Since then, the family has been greatly expanded through whole and segmental genome duplication events. During evolution, many amino acid changes have been introduced in individual chemokine receptors, but certain motifs and residues are highly conserved. Previously, we proposed a nomenclature system of the vertebrate chemokine receptors based on their evolutionary history and phylogenetic analyses. With the use of this classification system, we are now able to confidently assign the species orthologs of vertebrate chemokine receptors. Here, we systematically analyze conserved motifs and residues of each group of orthologous chemokine receptors that may play important roles in their signaling and biologic functions. Our present analysis may provide useful information on how individual chemokine receptors are activated upon ligand binding.